226Ra determination via the rate of 222Rn ingrowth with the Radium Delayed Coincidence Counter (RaDeCC). (15th November 2013) - Geibert, Walter; Rodellas, Valentí; Annett, Amber; van Beek, Pieter; Garcia‐Orellana, Jordi; Hsieh, Yu‐Te; Masque, Pere
<x xml:space="preserve">Abstract</x> We present a new method to determine 226Ra in aqueous environmental samples, based on the rate of ingrowth of 222Rn from 226Ra, using the radium delayed coincidence counter (RaDeCC). We use the same instrument setup that is used for the determination of 223Ra and 224Ra. In contrast to methods published earlier, the approach does not require a modification of the counting equipment, counting separately for 226Ra, or waiting for radioactive equilibrium. We show that the calibration works from as low as 10 dpm (0.166 Bq) per sample, up to more than 1000 dpm (16.7 Bq). Although uncertainties are larger (typically around 10%) than reported uncertainties for γ counting, liquid scintillation, or mass spectrometry at comparable activities, the simple setup, low cost, and robustness of the method make it a useful approach for underway measurements, combinations with short‐lived radium isotopes, or monitoring purposes when limited funding or infrastructure is available.